PHYTOCHEMICAL, PHYSICOCHEMICAL, AND FLUORESCENCE ANALYSIS OF LEAF EXTRACT OF SYZYGIUM CALOPHYLLIFOLIUM WALP. - Nagulan, Sumithra; Kumar, Sevanan Rajesh (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: The aim of the study is to investigate the phytochemical, physicochemical, and fluorescence analysis of Syzygium calophyllifolium Walp. leaf extract. Methods: The plant powder was extracted with different solvents such as petroleum ether, benzene, ethyl acetate, methanol, ethanol, and water. The different extracts were tested qualitatively for the identification of various phytochemical constituents. The plant powder was subjected to fluorescence analysis in daylight and in ultraviolet-light (254 nm and 365 nm). Results: Water soluble extractive value was found to be higher than ethanol, methanol, acetone, petroleum ether, benzene, and chloroform. The total ash value was observed 10.84Â±0.13. The result showed the presence of secondary metabolites such as alkaloid, anthraquinone, catechin, coumarin, flavonoid, phenol, quinone, saponin, steroid, tannin, terpenoid, sugar, glycoside, xanthoprotein, and fixed oil. Conclusion: It can be concluded from the present study the leaves of S. calophyllifolium contain various phytochemical constituents which may be used as phyto medicines. Keywords: Syzygium calophyllifolium, Eugenia calophyllifolia, Myrtaceae, Phytochemical screening, Physicochemical constant, Flourescence analysis.